KONTRIBUSI MANAJEMEN SUMBER DAYA MANUSIA (SDM) TERHADAP PEMBERDAYAAN ENTERPRENEURSHIP SANTRI DI PESANTREN MODERN TGK. CHIEK OEMAR DIYAN INDRAPURI ACEH BESAR - Zuliani Zuliani; Zulfahmi Zulfahmi; Ilham Hidayatullah (Departemen Manajemen, Universitas Syiah Kuala, 2018)
This article attempts to present the contribution of human resource management to entrepreneurship empowerment of students. This study aims to determine the understanding, independence and competitiveness of students in entrepreneurship by using a qualitative approach that is field (field research). Research location at Modern Islamic Boarding School Tgk. Chiek Oemar Diyan Aceh Besar with data collection methods through interviews and questionnaires then analyzed descriptively. The results showed that most of the students had a simple understanding of entrepreneurship both in terms of planning and implementation. In terms of independence, it can also be seen internally at an adequate level, while externally individuals are still lacking. In addition, the competitiveness of santri is still low, it is found that santri lack confidence and insight to create jobs. Finally, it can be said that there is a contribution of Modern Pesantren Tgk. Chiek Oemar Diyan in human resource management has given birth to students who are entrepreneurial with no religious knowledge. Key words: Human Resource Management (HR), Entrepreneurship, Santri